Integrating teenage population into environment management in coastal communities in Cuba, trough educommunication and participative video - Pedroso Aguiar, Willy (2017)
Educommunication is a way of educative communication that promotes group learning from, trough and for communication. This paper systematizes two educommunicative experiences dealing with environmental issues, implemented by the Faculty of Communication of the University of Havana, in a collaboration project with the Cuban Environment Agency. As a result, it describes the methodological perspectives used, and the characteristics of the lived process emphasizing the roll of video and the learned lessons. It also highlights the importance of educommunication for integrating teenage population into environment management process.